Biochemical and Histological Study of Rat Liver Injury Induced by carbon tetrachloride (CCl4) - Ansam Awad Ali (Wasit Journal for Pure Sciences)
:        The liver is a vital organ that plays a key role in the detoxification of endogenous and exogenous, current study aimed to evaluate the toxic effect of carbon tetrachloride (CCl4) on the liver structure substances, Thirty-four male Sprague Dawley rats at the age of (8-10 weeks) were used. The experiment was carried out by dividing the animals into six groups (T1, T2, T3, T4, T5A, T5B, T5C, T6), and each group contained five animals. Liver damage was stimulated in the groups (T1, T2, T3) synergistically between the damage-inducing substance CCL4. The amino acid BABA is in different concentrations (100, 150, 200) for BABA for five weeks in two doses. In the fourth group, T4, or giving it only CCL4 also twice a week for five weeks. As for the fifth group, T5, which was divided into (A, B, and C), it was given only the amino acid BABA in different concentrations (100, 150, 200). Nine animals were placed in this group, three animals for each group, while keeping the sixth group, T6, for control, as it was given only a physiological solution. Levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and bilirubin and histology of the liver were evaluated. The ALT( alanine aminotransferase), AST (aspartate aminotransferase) and bilirubin showed high mean levels in T4 group (132.8±28.09,138.9±6.09, 3.88±1.60), respectively. while showed  low level in T5C group (93.7±5.03,68.9±5.52, 2.12±0.93) and control group (91.2±4.87 ,70.1±3.15, 0.91±0.46), respectively. a positive correlation showed  between bilirubin and ALT(0.408*), bilirubin and AST(0.459**) and between ALT and AST(0.769**).  A section of the liver of group (T4) rats treated with carbon tetrachloride, showed the pathological anatomical shapes of the hepatic lobules showed severe congestion in the portal vein, and a noticeable disorder in the hepatic cord characterized by severe fatty degeneration of the liver cells with Atrophy, congestion and congestion of central veins, portal vessels and normal liver cells. The current study concluded the relationship between the increase in liver enzyme in the case of treatment with CCl4 and its decrease in treatment with the amino acid BABA. High dosages of CCl4 exhibited liver function impairment due to heightened levels of enzymatic biomarkers, specifically ALT and AST, which correlate with the extent of liver damage and dysfunction.